THE EFFECTIVENESS OF THE SCRAMBLE LEARNING MODEL TO INCREASING LEARNING MOTIVATION IN THE SKI SUBJECT STUDENT OF XII IPA 2 MAN AMBON - La Zubair Zubair; Syamsuar Hamka Hamka (IAIN Ambon, 2022)
This study aims to determine the effectiveness of the scramble learning model in increasing student motivation in SKI subjects on Islamic kingdoms in Indonesia for class XII IPA 2 MAN Ambon. This study uses a type of participant class action research, which is carried out in stages until the researcher gets results that are in accordance with the treatment or actions in the class. So, researchers will act actively during the research process. This classroom action research consists of three parts, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. After planning, the researcher then performs pre-action by collecting data, then carrying out the action in several cycles then he analyzes the data so that it becomes a research report. The results in this study indicate that the learning process using the scramble learning model has experienced effectiveness in increasing student learning motivation in the subject of Islamic cultural history subject to Islamic kingdoms in Indonesia, class XII IPA 2 at Ambon State Madrasah Aliyah, Academic Year 2022/2023. By obtaining data through the percentage of the average value of student learning motivation in cycle I of (68.7%) with this result increasing student motivation experienced a change from the previous condition, namely pre-cycle with an average score of (37.4%) even though it had not yet reached the completeness criterion of learning motivation of (75%). In cycle II, the average mastery score of students' learning motivation was (89.5%) with this result that students experienced a very good increase in learning motivation and met the mastery criteria for an average score of (75%) which was the main target in class action research (CAR) through the scramble learning model.